Global economic prospects : June 2020 - World Bank Group (Washington World Bank Group, 2020)
The COVID-19 pandemic has, with alarming speed, dealt a heavy blow to an already-weak global economy, which is expected to slide into its deepest recession since the second world war, despite unprecedented policy support. The global recession would be deeper if countries take longer to bring the pandemic under control, if financial stress triggers defaults, or if there are protracted effects on households and firms. Economic disruptions are likely to be more severe and protracted in emerging market and developing economies with larger domestic outbreaks and weaker medical care systems; greater exposure to international spillovers through trade, tourism, and commodity and financial markets; weaker macroeconomic frameworks; and more pervasive informality and poverty. Beyond the current steep economic contraction, the pandemic is likely to leave lasting scars on the global economy by undermining consumer and investor confidence, human capital, and global value chains. Being mostly a reflection of the recent plunge in global energy demand, low oil prices are unlikely to provide much of a boost to global growth in the near term. While policymakers' immediate priorities are to address the health crisis and moderate the short-term economic losses, the likely long-term consequences of the pandemic highlight the need to forcefully undertake comprehensive reform programs to improve the fundamental drivers of economic growth, once the crisis abates.
Keywords: Petroleum industry and trade-Economic aspects; Economic forecasting